(untitled) (Scientific journal of the Fergana State University, 2024)
This article highlights the study of the problem of developing knowledge of the spiritual and moral competence of students in the philosophical and pedagogical literature; the author reveals the essence of the concepts of “upbringing-upbringing”, the spiritual and moral competence of students, based on an analysis of theoretical material.